2014
DOI: 10.1002/acp.3004
|View full text |Cite
|
Sign up to set email alerts
|

Disfluency Meets Cognitive Load in Multimedia Learning: Does Harder‐to‐Read Mean Better‐to‐Understand?

Abstract: In a series of four experiments, we examined the impact of disfluency in multimedia learning by testing contrasting predictions derived from disfluency theory and cognitive load theory against each other. Would a less legible text be beneficial to learning when accompanied by pictures, and what would be the role of less legible pictures? Students (N = 308) learned with text and pictures that were either easy-to-read (i.e., fluent) or harder-to-read (i.e., disfluent) about how a toilet flush works (Experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 47 publications
4
84
1
Order By: Relevance
“…The fact that we did not observe a significant direct effect of disfluency on text comprehension is in line with other recent findings (Eitel & Kühl, 2016;Eitel et al, 2014;Lehmann et al, 2016;Rummer et al, 2016;Strukelj et al, 2016). However, we have shown that disfluency has an indirect effect on text comprehension by reducing MW, thereby elucidating one mechanism by which disfluency influences the reading process.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that we did not observe a significant direct effect of disfluency on text comprehension is in line with other recent findings (Eitel & Kühl, 2016;Eitel et al, 2014;Lehmann et al, 2016;Rummer et al, 2016;Strukelj et al, 2016). However, we have shown that disfluency has an indirect effect on text comprehension by reducing MW, thereby elucidating one mechanism by which disfluency influences the reading process.…”
Section: Discussionsupporting
confidence: 92%
“…pagewanted=all&_r=0). However, to the best of our knowledge, only a few published studies were able to confirm the basic effect in conceptual replications (French et al 2013;Sungkhasettee et al 2011;Weltman and Eakin 2014) whereas other studies found null effects or even negative effects of degraded text fonts on learning outcomes (e.g., Eitel et al 2014;Miele et al 2013;Yue et al 2013). Given the high number of studies citing the DiemandYauman et al article, the lack of published studies replicating the original effect is surprising.…”
Section: Introductionmentioning
confidence: 79%
“…Eitel et al (2014) conducted four experiments and found a positive disfluency effect only in the first of four experiments, so that the overall pattern of results was clearly in favor of a null effect of disfluency (shown by Bayesian analysis). Interestingly, though, results for reported mental effort paralleled results for performance in the studies of Eitel et al (2014). Only in the first of four experiments, more mental effort was reported for disfluent texts, suggesting a relation between mental effort and performance.…”
Section: Disfluency and Learning With Complex Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the experience of fluency in learning situations correlates with a sense (or the explicit judgment) that information has been easily acquired, it is not always correlated with actual learning (e.g., Bertsch, Pesta, Wiscott, & McDaniel, 2007;Bjork, 1994;Carpenter et al, 2013;Carpenter, Mickes, Rahman, & Fernandez, 2016;Eitel, Kuhl, Scheiter, & Gerjets, 2014;Hirshman & Bjork, 1988;Leutner, Leopold, & Sumfleth, 2009;Rhodes & Castel, 2008;Sanchez & Khan, 2016;Slamecka & Graf, 1978;Yue, Castel, & Bjork, 2013). For this reason, if students base metacognitive evaluations of their learning on how fluently or easily they processed learning materials-but that experience of fluency is not correlated with their actual learning-then their self-assessments of their learning will be inaccurate.…”
Section: Fluency and Learningmentioning
confidence: 99%